Study on the structural stability of partial cable-stayed bridges with multiple towers and high piers during construction. - Chenglong Zhu; Lingbo Wang; Yixiang Liu; Lin Kang; Xinjun Guo; Xiaobo Zheng (PLoS ONE)
To clarify the structural safety and stability of partial cable-stayed bridges with multiple towers and high piers during the construction stage, a finite element analysis model of the entire construction process was established using a five-tower, six-span, partial cable-stayed bridge in Shaanxi Province, China, as the engineering background. Linear elasticity and nonlinear stability analyses were carried out in the following key construction stages: bare tower construction, maximum cantilever construction without cables, maximum cantilever construction with cables, side-span closure, secondary mid-span closure, mid-span closure, and second-phase paving. A sensitivity analysis of the structural parameters (the main tower stiffness, main pier stiffness, and main beam stiffness) was conducted. Furthermore, the impacts of the combination of the reduction of the main pier stiffness with two unfavorable factors (the detachment of the construction hanging basket and asymmetric construction on both sides of the main beam) on the construction safety and stability of the structure were explored. The results show that the stability coefficient of the structure during the entire construction process met the requirements of the corresponding specifications; the linear elastic stability coefficient at each stage was greater than 4.0, and the nonlinear stability coefficient was greater than 2.5. Moreover, the stability coefficient was found to be the smallest at the stage of maximum cantilever construction with cables, which was thus identified as the most unfavorable construction stage. The instability mode at each construction stage was found to be the longitudinal instability of the main pier. The structural parameter sensitivity analysis revealed that the change in the stiffness of the main pier had the greatest impact on structural stability, and the structural safety factor was found to be proportional to the stiffness of the main pier. Furthermore, the effects of multiple factors were found to intersect; under the combination of the reduction of the main pier stiffness with the two unfavorable factors, the stability coefficient of the structure was found to be greatly reduced by more than 15%. Therefore, during the construction of partial cable-stayed bridges with multiple towers and high piers, the stage of maximum cantilever construction with cables should be of primary focus, the maintenance and management of the piers should be strengthened, and the unfavorable factors should be avoided. The results of this study can provide a reference for the construction and design of similar types of bridges.